First record of the heart urchin Metalia persica (Mortensen, 1940) (Spatangoida: Brissidae) from the Chennai coast, India - Kanagaraj, Chamundeeswari; Mooi, Rich; Kumar, Deepak Samuel Vijay; Premachandran, Hrishikesh; Rajendran, Abhilash Kottarathil; Rethinavelu, Sankar; Ramachandran, Purvaja; Ramachandran, Ramesh (Zootaxa, 2019)
The irregular urchin, Metalia persica (Mortensen, 1940), a heart urchin of the family Brissidae, is reported for the first time from the southeastern coast of India. A single specimen was collected from fishing by-catch at Chinna Neelankarai (12º 56’ 29.7” N, 80º 15’ 36.6” E), Chennai on April 5, 2018. Metalia persica was previously recorded only from the Persian Gulf (Arabian Gulf). This study records Metalia persica for the first time from Indian waters, in the Bay of Bengal, and elucidates features of the anal fasciole.